Pengembangan Media Pembelajaran Berbasis Website untuk Memfasilitasi Pemahaman Konsep Siswa SMK Negeri 5 Pekanbaru - Novialdi Novialdi; Zubaidah Amir MZ; Musa Thahir (Lembaga Anotero Scientific Pekanbaru, 2020)
This research aimed at producing an instructional media website based that was valid, practical, and able to facilitate student mathematics concept comprehension at State Vocational High School 5 Pekanbaru. ASSURE (Analyze learners, State objectives, Select method, media, and materials, Utilize method, media, and materials, Require learners participation, and Evaluate/revise) model was used. The subjects of this research were 37 students, and the object was the instructional media website based. The data were quantitative and qualitative. Validity and practicality test questionnaires, and concept comprehension test question were the instruments of collecting the data. The data obtained were analyzed by using Descriptive analysis technique. Based on validity test, the instructional media website based was stated on valid category with 88.13% validity level percentage. It was stated on practical category with 87.42% practicality level percentage. It facilitated student mathematics concept comprehension with 84.64% (very good) mastery percentage based on the mathematic concept comprehension test. Based on these results, it could be identified that the instructional media developed was valid, practical, and able to facilitate student mathematics concept comprehension at State Vocational High School 5 Pekanbaru.